Development of Quizizz-based Assessment Instruments for Grade IV Elementary Students - Wahidah, Miftahul; Hadikusuma Ramadan, Zaka (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
The present study sets out to design an assessment tool using Quizizz to evaluate understanding of the values and meaning of Pancasila among fourth-grade elementary students. The study applied the ADDIE development framework, which consists of five key steps: Analysis, Design, Development, Implementation, and Evaluation. According to assessments by two language experts, the instrument was deemed highly valid and dependable. The first expert assigned an average score of 81%, while the second gave 90%, resulting in an overall average of 85%, placing the tool in the "very valid" category. Additionally, an evaluation by an assessment specialist produced a validation score of 94%. The instrument’s reliability was tested through the Quizizz platform with 26 fourth-grade students, yielding Cronbach’s Alpha values of 0.774, 0.753, and 0.734. As all scores surpassed the accepted threshold of 0.7, it can be concluded that this tool is proper to use in assessing students' comprehension of Pancasila’s values and significance.